Composite metal bipolar plate and preparation method and application thereof

By combining the two-dimensional stainless steel plate with the three-dimensional mesh structure of titanium mesh and using explosive composite and rolling processes, the problem of poor corrosion resistance of existing metal bipolar plates is solved, and efficient and low-cost composite metal bipolar plate preparation is achieved, which improves its performance in fuel cells.

CN119839580APending Publication Date: 2025-04-18HUNAN FORHOME COMPOSITE MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510049189.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing metal bipolar plates have poor corrosion resistance during long-term use, and the processing and preparation of composite bipolar plates is complex, with high cost and poor material bonding.

Method used

A composite metal bipolar plate with a three-dimensional stainless steel plate and a titanium mesh structure is used to combine two-dimensional stainless steel plates with three-dimensional mesh structures. Through explosion composite and subsequent homogenization treatment and rolling, a composite metal bipolar plate with high conductivity, corrosion resistance and breathability are obtained.

Benefits of technology

The low-cost and efficient preparation of composite metal bipolar plates is achieved, the interface bonding strength of the material is improved, and the excellent performance in fuel cells is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119839580A_ABST
    Figure CN119839580A_ABST
Patent Text Reader

Abstract

The invention discloses a composite metal bipolar plate and a preparation method and application thereof. The composite metal bipolar plate is composed of a bipolar plate stainless steel base material and a titanium mesh porous conductive layer. According to the method, the explosive cladding plate is prepared in an explosive cladding mode, then the composite metal bipolar plate is obtained through homogenization treatment and rolling, the composite metal bipolar plate prepared through the method is tightly combined, the conductive layer is evenly distributed on the surface of the base material, and the bipolar plate has excellent conductivity, corrosion resistance and air permeability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of fuel cells, and in particular relates to a composite metal bipolar plate and a preparation method and application thereof. Background Art

[0002] Proton exchange membrane fuel cells convert chemical energy into internal energy through chemical reactions, and have been widely studied for their small size, high energy density, and zero pollution. As one of the important components of fuel cells, bipolar plates not only avoid direct contact between the anode and cathode, but also play an important role in conducting electrons, supporting membrane electrodes, and dissipating heat and draining water. The bipolar plates currently used are mainly divided into three categories: graphite bipolar plates, metal bipolar plates, and composite bipolar plates. Metal bipolar plates have been widely used in high-power fuel cells because their forming performance in an ultra-thin state is better than other materials.

[0003] Metals are excellent conductors of heat and electricity, and also have good mechanical strength. Commonly used metal bipolar plate materials include aluminum alloy, titanium alloy, stainless steel and foam metal. However, single metal bipolar plates have the disadvantage of poor corrosion resistance and are difficult to meet the long-term use of fuel cells. Generally, composite metal bipolar plates are complex to process and prepare, with high costs and poor material bonding. Summary of the invention

[0004] According to the shortcomings of the prior art, the first object of the present invention is to provide a method for preparing a composite metal bipolar plate. The preparation method provided by the present invention is simple and controllable, and is suitable for industrial large-scale production.

[0005] The second object of the present invention is to provide a composite metal bipolar plate prepared by the above-mentioned preparation method. The composite metal bipolar plate provided by the present invention is composed of a two-dimensional stainless steel plate and a three-dimensional titanium mesh with a mesh structure, thereby ensuring the conductivity, corrosion resistance and air permeability of the metal composite bipolar plate.

[0006] The third object of the present invention is to provide an application of a composite metal bipolar plate, and to use the composite metal bipolar plate in a fuel cell.

[0007] In order to achieve the above object, the present invention adopts the following technical solution: The present invention discloses a method for preparing a composite metal bipolar plate. The method comprises the following steps: laying a titanium mesh on a platform and placing a support frame on the surface of the titanium mesh. Then, a stainless steel plate is placed on the support frame and explosives are laid to perform explosive composite to obtain an explosive composite plate. Then, the explosive composite plate is firstly homogenized and then rolled to obtain the composite metal bipolar plate.

[0008] The preparation method of the present invention obtains the composite metal bipolar plate by explosive compounding and then rolling, which has low cost and high interface bonding strength of the obtained composite metal bipolar plate.

[0009] In a preferred solution, the stainless steel plate is first subjected to surface grinding treatment to remove the surface oxide layer and passivation layer to obtain a smooth stainless steel plate with good flatness, thereby ensuring high-precision explosive lamination.

[0010] In a preferred solution, the thickness of the stainless steel plate is 0.5-2 mm. In order to meet the thickness requirements of the bipolar plate in the present invention, a thinner stainless steel plate is required, but it cannot be too thin, as it will affect the effect of the explosive compounding process, while too thick will certainly be detrimental to the subsequent rolling.

[0011] In a preferred solution, the thickness of the titanium mesh is 0.5-1.5 mm. In order to meet the thickness requirements of the bipolar plate in the present invention, a thinner titanium mesh is also required, but it cannot be too thin, as it will affect the effect of the explosive composite process, while too thick will certainly be detrimental to the subsequent rolling.

[0012] In a preferred solution, the height of the support frame is 2-4 mm. In the present invention, the height of the support frame needs to be effectively controlled. If the height of the support frame is too low, the explosive force will be too large, and the excessive explosive force will cause the net to be embedded in the plate, and the plate will also be deformed. If the height of the support frame is too high, the explosive force will be insufficient.

[0013] According to a preferred solution, when laying the explosives on the stainless steel plate, the explosives are controlled to be laid only above the explosive grid lines.

[0014] In the present invention, during the laying process of explosives, since the substrate is a mesh structure, when laying explosives on the surface of the composite plate, i.e., the stainless steel plate, it is ensured as much as possible to be aligned and even with the grid lines of the underlying titanium mesh, to ensure direct contact between the mesh and the plate rather than contact between the mesh and the plate in the gaps during the explosive composite process. In actual operation, the substrate is placed above the composite plate, and lines are drawn on the composite plate through projection to obtain grid lines of explosives.

[0015] In a preferred solution, the laying thickness of the explosive is 0.1-0.2 cm. In the present invention, the amount of explosive is controlled to be 50%-70% of the amount used for explosive bonding between conventional plates. Within this range, the final explosive bonding effect is optimal.

[0016] In a preferred embodiment, the explosives are composed, by mass percentage, of 70-75% expanded ammonium nitrate, 10-12% No. 2 rock ammonium nitrate explosive, 5-8% porous ammonium nitrate, 3-4% diesel, 2-3% powdered emulsion explosive, and 3-4% salt.

[0017] Preferably, the detonation velocity of the explosive is 1500-2000 m / s.

[0018] In the present invention, by using the low detonation velocity explosive of the present invention, the amount of explosive and the laying method, the stainless steel plate and the titanium mesh can be metallurgically bonded, while preventing the mesh from being embedded in the plate and deforming.

[0019] In a preferred solution, the temperature of the homogenization treatment is 450-600° C. and the homogenization treatment time is 8-12 hours. The composite material obtained by the explosive compounding is subjected to homogenization heat treatment and then cooled.

[0020] In a preferred embodiment, the rolling is cold rolling, and the rolling process is to first perform 3-6 passes of rough rolling, and then perform 4-7 passes of finish rolling, wherein the deformation of the rough rolling pass is 13-17%, the total deformation is 80-86%, and the deformation of the finish rolling pass is 10-12%. The cold rolling process is controlled to reduce the thickness until the desired thickness is obtained, and the performance of the composite metal bipolar plate obtained is optimal. In the actual operation process, the finished product is also cut according to the size to obtain the composite metal bipolar plate.

[0021] The present invention also provides a composite metal bipolar plate prepared by the above preparation method, wherein the composite metal bipolar plate is composed of a bipolar plate stainless steel substrate and a titanium mesh porous conductive layer.

[0022] In a preferred embodiment, the thickness of the composite metal bipolar plate is 0.1-0.2 mm, the thickness of the stainless steel substrate of the bipolar plate is 0.05-0.1 mm, and the thickness of the porous conductive layer of the titanium mesh is 0.05-0.1 mm.

[0023] The present invention also provides an application of a composite metal bipolar plate prepared by the above preparation method, and the composite metal bipolar plate is used in a fuel cell.

[0024] Beneficial Effects

[0025] (1) The two-dimensional stainless steel plate and the three-dimensional titanium mesh are composited as fuel cell bipolar plates to ensure the conductivity, corrosion resistance and air permeability of the metal composite bipolar plates.

[0026] (2) The titanium mesh with a surface mesh structure not only improves the anti-corrosion performance, but also provides a place for the flow of gas, thereby increasing the reaction rate of the fuel cell to a certain extent.

[0027] (3) Explosive bonding is a technique that uses explosives to weld metals. It can bond metals with very different properties such as melting point, strength, and thermal expansion coefficient. It can also avoid the formation of brittle metal compounds. The materials bonded by explosive bonding are tightly bonded and are widely used. The present invention uses explosive bonding to bond stainless steel and titanium mesh and use them as composite metal bipolar plates, achieving good corrosion resistance and conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a schematic diagram of the front view of the composite metal bipolar plate.

[0029] Figure 2 A side view of a composite metal bipolar plate. DETAILED DESCRIPTION

[0030] In order to make the technical problems to be solved, technical solutions and advantages of the present invention more clear, they are described in detail below in conjunction with specific embodiments.

[0031] Example 1 A stainless steel plate and a titanium mesh with thicknesses of 1 mm and 1 mm respectively were selected, and the surface of the stainless steel plate was polished to remove impurities, oxide layers and passivation layers on the surface. The titanium mesh was placed on a platform, and a support frame was evenly placed on its surface, and the height of the support frame was 3 mm. Then the treated aluminum plate was placed on the support frame, and 0.1 cm thick explosives were laid on the stainless steel plate. The explosives, by mass percentage, were composed of 75% expanded ammonium nitrate, 10% No. 2 rock ammonium nitrate explosive, 5% porous ammonium nitrate, 4% diesel, 3% powdered emulsion explosive, and 3% salt; and an explosively composite stainless steel-titanium composite metal plate was obtained. The stainless steel-titanium composite metal plate was homogenized at 500°C for 10 hours, and then the obtained composite metal plate was rolled, first 5 rough rolling passes and then 6 finish rolling passes, the deformation amount of the rough rolling pass was 17%, and the deformation amount of the finish rolling pass was 12%. Subsequently, cutting was performed to finally obtain a stainless steel-titanium composite metal bipolar plate that met the requirements, with a thickness of 0.2 mm, wherein the thickness of the bipolar plate stainless steel substrate was 0.1 mm, and the thickness of the titanium mesh porous conductive layer was 0.1 mm.

[0032] The performance of the composite metal bipolar plate obtained in this Example 1 is shown in Table 1.

[0033] Example 2 Stainless steel plates and titanium mesh with thicknesses of 0.5 mm and 0.5 mm respectively were selected, and the surface of the stainless steel plates was polished to remove impurities, oxide layers and passivation layers on the surface. The titanium mesh was placed on the platform, and a support frame was evenly placed on its surface. The height of the support frame was 2 mm. Then the treated aluminum plate was placed on the support frame, and 0.1 cm thick explosives were laid on the stainless steel plate. The explosives, by mass percentage, were composed of 75% expanded ammonium nitrate, 10% No. 2 rock ammonium nitrate explosive, 5% porous ammonium nitrate, 4% diesel, 3% powdered emulsion explosive, and 3% salt; the explosives were detonated to obtain explosively composite stainless steel-titanium composite metal plates. The stainless steel-titanium composite metal plates were homogenized at 450℃ for 10 h, and then the composite metal plates were rolled, first 3 passes of rough rolling and then 5 passes of finishing rolling. Subsequently, cutting was performed to finally obtain a stainless steel-titanium composite metal bipolar plate that met the requirements, with a thickness of 0.2 mm, of which the thickness of the bipolar plate stainless steel substrate was 0.1 mm and the thickness of the titanium mesh porous conductive layer was 0.1 mm.

[0034] The performance of the composite metal bipolar plate obtained in this Example 2 is shown in Table 1.

[0035] Example 3 A stainless steel plate and a titanium mesh with a thickness of 1 mm and 0.5 mm respectively were selected, and the surface of the stainless steel plate was polished to remove impurities, oxide layer and passivation layer on the surface. The titanium mesh was placed on the platform, and a support frame was evenly placed on its surface, and the height of the support frame was 2 mm. Then the treated aluminum plate was placed on the support frame, and a 0.1 cm thick explosive was laid on the stainless steel plate. The explosive, by mass percentage, was composed of: 75% expanded ammonium nitrate, 10% No. 2 rock ammonium nitrate explosive, 5% 94.5% porous ammonium nitrate, 4% diesel, 3% powdered emulsion explosive, and 3% salt; the explosive was detonated to obtain an explosively composite stainless steel-titanium composite metal plate. The stainless steel-titanium composite metal plate was homogenized at 500 °C for 8 h, and then the obtained composite metal plate was rolled, firstly 5 passes of rough rolling and then 5 passes of finish rolling, the deformation amount of the rough rolling pass was 17%, and the deformation amount of the finish rolling pass was 12%. Subsequently, cutting was performed to finally obtain a stainless steel-titanium composite metal bipolar plate that met the requirements, with a thickness of 0.2 mm, wherein the thickness of the bipolar plate stainless steel substrate was 0.14 mm, and the thickness of the titanium mesh porous conductive layer was 0.06 mm.

[0036] The performance of the composite metal bipolar plate obtained in this Example 3 is shown in Table 1.

[0037] Comparative Example 1 The other conditions are the same as those in Example 1, except that the height of the support frame is 6 mm. The performance of the composite metal bipolar plate obtained in this comparative example 1 is shown in Table 1.

[0038] Comparative Example 2 The other conditions are the same as those in Example 1, except that the height of the support frame is 1 mm. The performance of the composite metal bipolar plate obtained in this comparative example 2 is shown in Table 1.

[0039] Comparative Example 3 The other conditions were the same as those in Example 1, except that the thickness of the explosive was 0.3 cm. The performance of the composite metal bipolar plate obtained in this comparative example 3 is shown in Table 1.

[0040] The obtained embodiments and comparative examples were tested for conductivity, corrosion resistance and air permeability, and the measured results are listed in Table 1. From the data in Table 1, it can be seen that the composite bipolar plate obtained in the embodiments has excellent conductivity, corrosion resistance and air permeability, while the comparative example has parameters that are not within the scope of the present invention, so the performance is worse than that of the embodiments.

[0041]

Claims

1. A method for preparing a composite metal bipolar plate, characterized in that: The titanium mesh is laid on the platform and a support frame is placed on the surface thereof. Then a stainless steel plate is placed on the support frame and explosives are laid to perform explosive composite to obtain an explosive composite plate. The explosive composite plate is then homogenized and then rolled to obtain a composite metal bipolar plate.

2. The method for preparing a composite metal bipolar plate according to claim 1, characterized in that: The stainless steel plate is first subjected to surface grinding treatment.

3. The method for preparing a composite metal bipolar plate according to claim 1, characterized in that: The thickness of the stainless steel plate is 0.5-2 mm; The thickness of the titanium mesh is 0.5-1.5 mm; The height of the support frame is 2-4 mm.

4. The method for preparing a composite metal bipolar plate according to claim 1, characterized in that: When laying explosives on the stainless steel plate, control the explosives to be laid only above the explosive grid lines; The laying thickness of the explosive is 0.1-0.2 cm.

5. The method for preparing a composite metal bipolar plate according to claim 1 or 4, characterized in that: The explosive is composed of the following by mass percentage: 70-75% expanded ammonium nitrate, 10-12% No. 2 rock ammonium nitrate explosive, 5-8% porous ammonium nitrate, 3-4% diesel, 2-3% powdered emulsion explosive, and 3-4% salt; The detonation velocity of the explosive is 1500-2000m / s.

6. The method for preparing a composite metal bipolar plate according to claim 1 or 4, characterized in that: The temperature of the homogenization treatment is 450-600° C., and the time of the homogenization treatment is 8-12 hours.

7. The method for preparing a composite metal bipolar plate according to claim 1 or 4, characterized in that: The rolling is cold rolling, and the rolling process is to first perform 3-6 passes of rough rolling and then perform 4-7 passes of finish rolling. The deformation amount of the rough rolling passes is 13-17%, the total deformation amount is 80-86%, and the deformation amount of the finish rolling passes is 10-12%.

8. A composite metal bipolar plate prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The composite metal bipolar plate is composed of a bipolar plate stainless steel substrate and a titanium mesh porous conductive layer.

9. A composite metal bipolar plate prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The thickness of the composite metal bipolar plate is 0.1-0.2 mm, the thickness of the stainless steel substrate of the bipolar plate is 0.05-0.1 mm, and the thickness of the porous conductive layer of the titanium mesh is 0.05-0.1 mm.

10. Application of a composite metal bipolar plate prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The composite metal bipolar plate is used in a fuel cell.